2018
DOI: 10.1111/odi.12801
|View full text |Cite
|
Sign up to set email alerts
|

Dental properties, ultrastructure, and pulp cells associated with a novel DSPP mutation

Abstract: We identified a novel mutation in the DSPP gene which disturbed dentin characteristics and pulp cells' behaviours. Our study expands the mutation spectrum and understanding of pathologic dentin phenotypes related to the frameshift deletion in the dentin phosphoprotein (DPP) region of the DSPP gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…To date, most histomorphological studies have focused on the effects of DGI Type II on dentin phenotypes (2,3,7,18) but fail to connect other distinguishing features of the disease, such as the fact that the pulp is typically obliterated (3,7,12,(18)(19)(20)(21)(22). Why this is the case is not known, but one theory suggests that the failure of the enamel to remain attached to the dentin results in trauma to the pulp, and the tooth responds by secreting more dentin (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most histomorphological studies have focused on the effects of DGI Type II on dentin phenotypes (2,3,7,18) but fail to connect other distinguishing features of the disease, such as the fact that the pulp is typically obliterated (3,7,12,(18)(19)(20)(21)(22). Why this is the case is not known, but one theory suggests that the failure of the enamel to remain attached to the dentin results in trauma to the pulp, and the tooth responds by secreting more dentin (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The teeth often undergo rapid and severe attrition in DGI patients associated with DSPP mutations. It is generally believed that enamel readily chips off from the underlying defective dentin and/or abnormal DEJ after tooth eruption, thereby exposing the softer and malformed dentin to rapid attrition (Wright and Gantt, 1985;Kim et al, 2004;MacDougall et al, 2006;Hart and Hart, 2007;Kida et al, 2009;Min et al, 2014;Porntaveetus et al, 2018). However, it has also become evident that in some cases, the enamel itself may have intrinsic developmental defects (Lee et al, 2011;Wang et al, 2011;Bloch-Zupan et al, 2016;Taleb et al, 2018), which may be a direct contributing factor to rapid tooth wear observed in DGI patients.…”
Section: Discussionmentioning
confidence: 99%
“…The exfoliated lower right central incisor of the proband was investigated as previously described 11 . Briefly, tooth color was measured as L*a*b* scale by ShadeEye-NCC ® (Shofu Inc., Japan).…”
Section: Methodsmentioning
confidence: 99%